CP-206 Pharmacist consultation in adult patients treated with oral therapy in dermatology department: pharmacoeconomic study. (25th February 2017) - Boisseranc, C; Tabele, C; Correard, F; Mallet, S; Monestier, S; Hesse, S; Gaudy, C; Esteve, M-A; Bertault-Peres, P; Honore, S; Grob, JJ
Abstract : Background: Pharmacist consultations (PC) for patients with oral anticancer medication (OAM) are a real need. 1 According to the General Directorate of Care Offer (DGOS), a day hospital (DH) fee can be charged only if three consultations by different health care professionals are performed for each patient (Circular Frontier). Moreover, a new General Interest Mission (MIG) allows a refund of consultations for the first OAM prescription. Purpose: To assess the financial impact of PC conducted as part of a DH in dermatology. Material and methods: DH billing for melanoma or carcinoma patients treated with OAM is subject to completion of three consultations: medical (MC), pharmaceutical (PC) and clinician nurse consultations. Consultation of the electronic patient file has allowed us to bill each PC performed from 9 July 2015 to 8 July 2016, and to count the number of first OAM prescriptions. Results: Within 1 year, 225 PC were performed (83 patients) and billed as 46 MC and 163 DH, under the homogeneous group of sick 'Explorations and monitoring of skin diseases'. 16 PC were performed without charge, either during hospitalisation (OAM initiation), during PC (management of OAM's side effects) alone, during patient monitoring refusal or administrative oversights. Pharmacist/physician/clinician nurse collaboration enabled the refund of: 163 DH (DGOS funding), or €95 544.08 (€586.16/DH); and 57 consultations for first OAM prescription (MIG funding), or €5301 (€93/consultation). The mean gross annual salary plus social charges of a full time pharmacist (178 hours monthly) is €97 500. The mean duration of a PC is 30 min, representing 112.5 hours annually, or €5, 135. If MCs were performed without a PC, the refund would be €4564 (163 MC of €28 each). Overall, PC generated a profit of €85 845 € (via the DH billing) for the institution compared with a single MC. Conclusion: The implementation of PC in dermatology enabled the billing of DH, covering the pharmacist's pay and achieving profitability for the hospital. However, the introduction of a new MIG with the final objective to replace the Circular Frontier funding would make it less profitable, hence the need to upgrade the MIG rate. References and/or acknowledgements: JCO, ASCO2016;34:e18211. No conflict of interest